A ANALISIS KELAYAKAN ALAT SUCTION PUMP LABORATORIUM PERAWAT STIKES AL INSYIRAH PEKANBARU - Yeni Pertiwi; Nur Hadziqoh; Romi Mulyadi; Apriliani (Jurnal Ilmu Keperawatan, 2022)
Suction Pump is a medical device that is used to suck fluids formed by body secretions such as blood, saliva, pus, mucus and others. In addition to the hospital, this tool is also used in the nurse's laboratory as a clinical practice tool for nursing students. All medical devices must be calibrated periodically. In this study, we will discuss how to calibrate the suction pump with the aim of knowing whether the suction pump in the laboratory is suitable for use or not. The research was conducted using work methods that have been determined by the ministry of health, including physical inspection and tool functions, electrical safety and measuring tool performance with the power of calculation parameters. The results showed that the results of the physical examination and the function of the tool were 10%, electrical safety inspection was 32% and the measurement of the tool's suction power was 50% so that the overall inspection of the tool obtained a score of 92% with the status of the tool being fit for use.